Telecontrol of Prosthetic Robot Hand Using Myo Armband - Yakob M.Y.B.; Baharuddin M.Z.B.; Khairudin A.R.M.; Karim M.H.B.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
3D printers; Automation; Bionics; End effectors; Human robot interaction; Intelligent systems; Process control; Robotic arms; Control signal; Hand movement; Prosthetic arm; Prosthetic hands; Serial communications; Upper limb amputation; Wireless communications; Wireless control; Artificial limbs